The Pristine Survey – VIII. The metallicity distribution function of the Milky Way halo down to the extremely metal-poor regime. Issue 4 (16th January 2020) - Youakim, K; Starkenburg, E; Martin, N F; Matijevič, G; Aguado, D S; Allende Prieto, C; Arentsen, A; Bonifacio, P; Carlberg, R G; González Hernández, J I; Hill, V; Kordopatis, G; et al.
ABSTRACT: The Pristine survey uses narrow-band photometry to derive precise metallicities down to the extremely metal-poor regime ( [Fe/H] -3 ), and currently consists of over 4 million FGK-type stars over a sky area of 2500 deg^2 . We focus our analysis on a subsample of ∼80 000 main-sequence turn-off stars with heliocentric distances between 6 and 20 kpc, which we take to be a representative sample of the inner halo. The resulting metallicity distribution function (MDF) has a peak at [Fe/H] =-1.6, and a slope of Δ(LogN)/Δ [Fe/H] = 1.0 ± 0.1 in the metallicity range of -3.4 [Fe/H] -2.5 . This agrees well with a simple closed-box chemical enrichment model in this range, but is shallower than previous spectroscopic MDFs presented in the literature, suggesting that there may be a larger proportion of metal-poor stars in the inner halo than previously reported. We identify the Monoceros/TriAnd/ACS/EBS/A13 structure in metallicity space in a low-latitude field in the anticentre direction, and also discuss the possibility that the inner halo is dominated by a single, large merger event, but cannot strongly support or refute this idea with the current data. Finally, based on the MDF of field stars, we estimate the number of expected metal-poor globular clusters in the Milky Way halo to be 5.4 for [Fe/H] -2.5 and 1.5 for [Fe/H] -3, suggesting that the lack of low-metallicity globular clusters in the Milky Way is not due simply to statistical undersampling.